Efek Moderasi Loyalitas Nasabah Dengan Pengaruh Service Quality, Trust Dan Electronik Word Of Mouth Terhadap Customer Satisfaction Pengguna Bsi Mobile - Uslan, Sugianto; Fatimah, Siti (Jurnal Keuangan dan Perbankan Syariah, 2024)
The primary focus of this study is to examine how service quality, trust, and electronic word of mouth impact customer satisfaction. Additionally, customer loyalty is considered as a moderating factor influencing the relationship between these variables. This research employs a quantitative approach utilizing a Likert scale for measurement. The survey involved 100 respondents. Methodologically, the study includes classical assumption testing, multiple regression analysis, hypothesis testing, and moderated regression analysis (MRA) using SPSS version 25. The findings indicate a significant positive impact of service quality, trust, and electronic word of mouth on customer satisfaction. Moreover, customer loyalty effectively moderates these relationships, further enhancing customer satisfaction.